Numerical investigation towards implementation of punched winglet as vortex generator for performance improvement of a fin-and-tube heat exchanger. (March 2020) - Gupta, Arvind; Roy, Aditya; Gupta, Sachin; Gupta, Munish
Highlights: Numerical investigations to find the optimum configuration of punched out rectangular winglet with hole at their surface for performance improvement. Critical comparison is presented between punched and attached cases of rectangular winglet. Punched-out winglet gives up to 34% augmentation in heat transfer for common flow up configuration located upstream. Punched-out winglet enhances the augmentation by 73% over baseline case for common flow down configuration at upstream location. Abstract: Thermohydraulic performance of fin-tube heat exchanger can be augmented by using longitudinal vortex generators. Numerical simulations have been performed in the present work for investigating the effect of punching a rectangular winglet having hole from fin surface, on the heat transfer and flow resistance characteristics in a fin-tube heat exchanger. The mentioned concept is being studied in two configurations namely, common flow down and common flow up. Comparisons on the basis of heat transfer and flow resistance characteristics have been drawn between punched and non-punched cases of rectangular winglet with hole for all the configurations under consideration using Colburn's factor ( j ), friction factor ( f ) and performance evaluation criterion (PEC) also known as JF factor ( j1 /j0 )/( f1 /f0 ) 1/3 . Investigations have been performed considering Reynolds number in the range of 1500 to 9000 and angle of attack as 45°. Numerical simulations have been performed using SST k-ω turbulence model which has demonstrated capabilities of capturing separated flows. There is a heat transfer augmentation of up to 34% for the considered range of Reynolds number in case of fin-tube heat exchanger employing punched rectangular winglet with hole having Common Flow Up configuration located in the upstream location, over the non-punched case of winglet with hole in the same configuration and location. The result clearly indicates that punching the rectangular winglet having hole considerably improves thermohydraulic performance in case of winglet placed in common flow up configuration at upstream location.